Zoning of marine protected areas for biodiversity conservation in Bangladesh through socio-spatial data. (1st May 2019) - Sarker, Subrata; Rahman, Muhammad Mizanur; Yadav, Atul Kumar; Islam, Mohammad Mahmudul
Abstract: Marine protected areas (MPAs) have become one of the most widely employed marine management tools worldwide for conserving species and habitats, maintaining ecosystem functioning, and ensuring sustainable use of marine resources. In this study, we adopted a science-based, stakeholder-driven and ecosystem based approach to identify coastal and marine habitats for potential MPA declaration towards achieving Aichi target 11. In addition, we also proposed an integrated management approach for MPA management in Bangladesh. Primary data were collected through stakeholder consultations from the three coastal zones of Bangladesh and secondary data were collected from an extensive literature review. We developed a priority index to select the most important habitats for MPA declaration. Our analysis suggests five potential habitats within the maritime boundary of Bangladesh for MPA declaration. These habitats cover an area of 8838 km 2 which is about 7.5% of the total maritime area of Bangladesh. Declaration of the MPAs will contribute to conserve the nursing and breeding habitats of fishes, crabs and seabirds, and thus will protect the marine biodiversity. To achieve this goal, local community involvement is required. This study will serve as a baseline for declaring MPAs in a solid scientific way through community engagement. Highlights: MPA is the most widely employed marine management tools. Five potential habitats selected for MPA declaration in Bangladesh. These habitats cover 7% of total maritime area of Bangladesh. Local community involvement is required for a successful implementation of MPA.